2020
DOI: 10.15283/ijsc19097
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Reproducible Generation of Induced Neural Stem Cells from Human Somatic Cells by Defined Factors

Abstract: Background and Objectives: Recent studies have described direct reprogramming of mouse and human somatic cells into induced neural stem cells (iNSCs) using various combinations of transcription factors. Although iNSC technology holds a great potential for clinical applications, the low conversion efficiency and limited reproducibility of iNSC generation hinder its further translation into the clinic, strongly suggesting the necessity of highly reproducible method for human iNSCs (hiNSCs). Thus, in orderto deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…To date, iPSCs have been used to study various neurological diseases ( Kwak et al, 2020 ; Han et al, 2021 ), including amyotrophic lateral sclerosis (ALS) ( Dimos et al, 2008 ; Kabashi et al, 2010 ; Egawa et al, 2012 ), Alzheimer’s disease (AD) ( Táncos et al, 2016a ; Chandrasekaran et al, 2016 ; Ochalek et al, 2016 ; Hernández-Sapiéns et al, 2020 ; Raska et al, 2021a ; Raska et al, 2021b ), and Parkinson’s disease (PD) ( Ma et al, 2017a ; Wang et al, 2017a ; Ma et al, 2017b ; Ma et al, 2017c ; Ma et al, 2017d ). Dimos et al obtained the first human iPSCs from middle-aged and elderly ALS patients ( Dimos et al, 2008 ), and Egawa et al demonstrated that motor neurons generated from iPSCs from patients with TDP-43 mutations can form cytoplasmic aggregates typical of postdeath ALS neurons ( Egawa et al, 2012 ).…”
Section: Clinical Application Of Reprogrammingmentioning
confidence: 99%
“…To date, iPSCs have been used to study various neurological diseases ( Kwak et al, 2020 ; Han et al, 2021 ), including amyotrophic lateral sclerosis (ALS) ( Dimos et al, 2008 ; Kabashi et al, 2010 ; Egawa et al, 2012 ), Alzheimer’s disease (AD) ( Táncos et al, 2016a ; Chandrasekaran et al, 2016 ; Ochalek et al, 2016 ; Hernández-Sapiéns et al, 2020 ; Raska et al, 2021a ; Raska et al, 2021b ), and Parkinson’s disease (PD) ( Ma et al, 2017a ; Wang et al, 2017a ; Ma et al, 2017b ; Ma et al, 2017c ; Ma et al, 2017d ). Dimos et al obtained the first human iPSCs from middle-aged and elderly ALS patients ( Dimos et al, 2008 ), and Egawa et al demonstrated that motor neurons generated from iPSCs from patients with TDP-43 mutations can form cytoplasmic aggregates typical of postdeath ALS neurons ( Egawa et al, 2012 ).…”
Section: Clinical Application Of Reprogrammingmentioning
confidence: 99%
“…2). These cells, after being transplanted into the stem cell pool in the adult mouse brain, exhibited true pluripotency in terms of proliferation and differentiation into neurons and glial cells (81,82). The reprogramming efficiency was further improved by the addition of E47 or transcription factor 3 (83).…”
Section: Related Biological Processes Of Brn4mentioning
confidence: 99%
“…This approach is an appealing alternative to existing iPSC technology because it enables the production of patient-specific NSCs without passing through the pluripotent stage, thereby decreasing the tumorigenic risk (15,16). Since the first mouse iNSCs (miNSCs) were established in 2011 (12), many studies have been published detailing the derivation of iNSCs from a variety of species, including rats (17), monkeys (18), and humans (18)(19)(20). Established iNSCs have numerous features in common with embryonic brain-derived NSCs, including morphology, self-renewal capacity, gene and protein expression profiles, epigenetic state, as well as functional multipotency in vitro and in vivo (9,21,22).…”
Section: Introductionmentioning
confidence: 99%